2011
DOI: 10.1302/0301-620x.93b10.27224
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of frozen shoulder by manipulation under anaesthetic and injection

Abstract: The effect of timing of a manipulation under anaesthetic (MUA) and injection of corticosteroid and local anaesthetic for the treatment of frozen shoulder has attracted little attention to date. All studies describe a period of conservative treatment before proceeding to an MUA. Delay has been associated with a poorer outcome. We present a retrospective review of a prospectively collected, single-surgeon, consecutive series of 246 patients with a primary frozen shoulder treated by MUA within four weeks of pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 9 publications
1
45
2
Order By: Relevance
“…The average premanipulation range of motion was 69° in fl exion and 54° in abduction, suggesting that these patients were in their "frozen phase." A more recent retrospective analysis of 246 patients treated with MUA in their frozen phase revealed that the duration of symptoms and the OSS or the change in OSS had no correlation [ 51 ]. In this study, the mean duration of presenting symptoms was 28 weeks, ranging from 6 weeks to 156 weeks.…”
Section: Timing Of Muacontrasting
confidence: 54%
See 1 more Smart Citation
“…The average premanipulation range of motion was 69° in fl exion and 54° in abduction, suggesting that these patients were in their "frozen phase." A more recent retrospective analysis of 246 patients treated with MUA in their frozen phase revealed that the duration of symptoms and the OSS or the change in OSS had no correlation [ 51 ]. In this study, the mean duration of presenting symptoms was 28 weeks, ranging from 6 weeks to 156 weeks.…”
Section: Timing Of Muacontrasting
confidence: 54%
“…Numerous authors have reported no complications with this procedure [ 1 , 11 , 18 , 40 , 41 , 46 , 49 , 53 ]. Thomas et al performed MUA in 246 patients, in which there were no fractures or dislocations, no symptoms of acute rotator cuff tear, no neurological or other iatrogenic injuries [ 51 ]. Ibrahim et al reported one case of vasovagal episode during the procedure among 42 cases [ 20 ].…”
Section: Complicationsmentioning
confidence: 99%
“…This same study group has analyzed the effect of the timing of MUA on outcome further and has shown that the benefit of MUA is independent of the duration of symptoms, such that prolonging conservative management is not detrimental to the final outcome. 4 Given that we had quite a broad age range (25 years to 81 years), we were surprised that age did not make a significant difference to outcome over the short-or longterm, albeit that the younger age group tended to include the diabetic patients. This has not been analyzed further.…”
mentioning
confidence: 94%
“…Unfortunately, it remains not fully understood and this interesting subgroup of patients has had little attention in the literature to date to provide guidance on the natural history of their condition or their management. Having previously shown that treatment with MUA and injection in primary frozen shoulder results in good outcomes and is safe, 5 we cautiously treated this cohort of patients similarly.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Having previously found that treatment with an MUA and injection in primary frozen shoulder results in good outcomes and is safe, 5 we treated this group of patients similarly. There was however concern in this group of patients that the frozen shoulder or contracted capsule may help to provide some stability to the shoulder and that MUA and injection may actually induce recurrent instability of the shoulder joint by releasing the contracted capsule.…”
Section: Introductionmentioning
confidence: 99%